2017
DOI: 10.1080/10810730.2017.1324540
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Patient–Provider Communication on Quality of Life among African-American and White Cancer Survivors

Abstract: Prior research has demonstrated poorer patient-provider communication ratings among African American compared to White patients. The quality of patient-provider communication has been shown to impact treatment outcomes among cancer patients. A secondary data analysis design was used to determine the relationship of six patient-provider communication variables on the physical health quality of life (PHQOL) and mental health quality of life (MHQOL) of African American and White cancer patients (N = 479). We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…We also observed that black or African Americans had higher HRQOL than whites. Previous studies have found that African Americans have a better psychological HRQOL due to higher levels of spirituality and social support [40,41,42]. In our study, 33.3% of black or African Americans reported that they had an anxiety or depression problem, and 48.6% of whites reported that they had such issues (unpublished data).…”
Section: Discussionsupporting
confidence: 55%
“…We also observed that black or African Americans had higher HRQOL than whites. Previous studies have found that African Americans have a better psychological HRQOL due to higher levels of spirituality and social support [40,41,42]. In our study, 33.3% of black or African Americans reported that they had an anxiety or depression problem, and 48.6% of whites reported that they had such issues (unpublished data).…”
Section: Discussionsupporting
confidence: 55%
“…In 2016, there were an estimated 15.5 million cancer survivors in the United States, and the number is expected to reach 23.6 million by 2030 . Patient‐provider communication (PPC) plays a critical role in diagnosis, treatment, and prognosis of critical health conditions like cancer . Effective communication among cancer patients, survivors, caregivers, and providers facilitates shared decision making and fosters patient‐centered health outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Providers who are uninformed on medical cannabis, resistant to its usage, or unwilling to discuss its usage with patients emerged as a barrier to medical cannabis use, which has clinical implications for the patient–provider relationship and access to care. Patient–provider communication has been examined as a factor that can facilitate or impede access to care and has been found to impact treatment outcomes (Li et al, 2017), particularly when it involves discussion of stigmatized topics. Some participants reported that their providers dismissed requests to discuss medical cannabis (i.e., did not explain their positive or dissenting stances on medical cannabis use).…”
Section: Discussionmentioning
confidence: 99%